Information Systems in the Era of the Internet of Things: A Domain-Specific Modeling Language - Strobel, Gero (Proceedings of the 54th Hawaii International Conference on System Sciences (HICSS), 2021)
Based on the technological developments of the last few years and the associated digitalisation, the Internet of Things is now an essential part of practically every aspect of life. Smart products with their sensors and actuators are not only boundary objects between the physical and digital world, but also tie both worlds more and more together. The capabilities of the products range from simple monitoring tasks by drones in agriculture to autonomous use in mining. However, in order to exploit the full potential of these capabilities, it is not enough to use individual smart products or sensors, it is necessary to develop holistic IoT-based information systems from the ground up. To take such a systemic perspective, it is essential to have a sound conceptual understanding of the domain and a common language. Against this background, the publication presents a domain-specific modelling language for IoT-based information systems.
Keywords: Internet of Things; Information System Architecture; Informationssystem Architektur; Domain Specific Modelling Language